Land Use Potential on Water Balance Based on SWAT Method in Saddang Watershed in Bendung Benteng Irrigation System - I. Irmayani; Muh. Ikbal Putera; Syahirun Alam; Suryansyah Surahman; M. Masnur (Universitas Sembilanbelas November Kolaka, 2018)
Saddang Watershed (DAS) as a large watershed in Sulawesi, rich in natural resource potential in the form of land, topography, slope, geology, soil, vegetation, climatology; rainfall, temperature, humidity, and sunshine. In maintaining and utilizing (watershed management) availability and water requirements for; humans, plants and animals. The availability and demand of water in watershed management requires the role of land in regulating agroclimatology and hydrology conditions. The water balance approach method used is SWAT (Soil and Water Assessment Tool) method of soil and water assessment tools, to determine the condition of availability and demand of water in an effort to maintain water flow conditions at all times (number and distribution) of Bendung Benteng irrigation system, which is capable of supply water for paddy field irrigation in two regencies of South Sulawesi’s paddy granaries namely Pinrang Regency and Sidrap Regency. According to the Schmidth-Fergusson climate classification, the type of climate in Saddang watershed area belongs to type C climate = slightly wet area with tropical rainforest vegetation, the average amount of rainfall ranges from 2.155 mm/year. This indicates that there is large level of rainfall every year and land use with a forest area of 676,39 or 26,41% of the watershed area, thus Saddang watershed is able to save tremendous amount of water supply. Based on the results of the water balance analysis using SWAT method, the amount of water available in the average watershed ; 3.133 mm year-1, the amount of water being flowed ; 1.040,9 mm, and stored as ground water ; 29,60 mm, as well as direct runoff ; 366,9 mm and flow coefficient of 0,45. Hence, there is 45% of the flow loss as surface stream and there is 55% of the flow stored in the watershed, and the model application is categorized as good both in conducting simulations and validating the flow discharge on Saddang River. Watershed processing classified as having good watershed conditions, because one indicator of a watershed's water performance can be seen from the river discharge fluctuation. River discharge fluctuations can be seen from the river regression coefficient (KRS), which is a number that shows ratio between maximum discharge (Qmax) and minimum discharge (Qmin). The highest discharge (Qmax) was 30.805 m³/sec while the lowest discharge (Qmin) was 994 m³/sec. The regression coefficient value (KRS) of Saddang River watershed was 26.650 m³/sec. Based on the results of the 2017 data analysis, the condition of Saddang watershed provides surplus value of 1.911.986 (m3 year-1), out of the total water availability of 2.155.273 (m3 year-1) minus the total irrigation water requirement of 243.286,50 m3 year-1, with the pattern of planting paddy-paddy-secondary crops (palawija). Therefore, Saddang watershed has the ability to store large amounts of water throughout the year